Phaeosphamides A and B, Cytotoxic Cyclodecadepsipeptides from the Mangrove-Derived Fungus Phaeosphaeriopsis sp. S296 - Siwen Niu; Jianlin He; Shuhuan Huang; Shouyuan Wu; Ling Zeng; Juan Wang; Bihong Hong; Ziming Chen (Marine Drugs, 2022)
Chemical examination of the fermented broth of the mangrove-derived fungus Phaeosphaeriopsis sp. S296 resulted in the isolation of two new cyclodecadepsipeptides, namely phaeosphamides A (1) and B (2), as well as one known congener Sch 217048 (3). The structures of new metabolites, including absolute configurations, were established on the basis of extensive spectroscopic data analyses, chemical conversion, and Marfey’s method. The 2-hydroxy-3-methylpentanoic acid (Hmp) moiety and pipecolic acid (Pip) unit in structures were rarely discovered in nature. Interestingly, compounds 1–3 are examples of peptides discovered from the fungal genus Phaeosphaeriopsis for the first time. All identified compounds were evaluated for their cytotoxicity against five tumor cell lines of AGS, BEL-7402, HepG2, B16, and BIU87. Among them, compound 1 showed inhibitory activities against these tumor cell lines with IC50 values ranging from 5.14 to 66.38 μM. A further mechanistic investigation found that 1 arrested AGS cells in the G2 phase and induced their apoptosis in a dose-dependent manner.